2015
DOI: 10.1155/2015/570541
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress due to a Natural Disaster Predicts Adiposity in Childhood: The Iowa Flood Study

Abstract: Prenatal stress can affect lifelong physical growth, including increased obesity risk. However, human studies remain limited. Natural disasters provide models of independent stressors unrelated to confounding maternal characteristics. We assessed degree of objective hardship and subjective distress in women pregnant during severe flooding. At ages 2.5 and 4 years we assessed body mass index (BMI), subscapular plus triceps skinfolds (SS + TR, an index of total adiposity), and SS : TR ratio (an index of central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 43 publications
1
78
0
Order By: Relevance
“…(Note, studies evaluating fetal weight and birth weight were included in the Fetal/Neonatal Health section.) In the Iowa Flood Study ( N  = 106), there was no evidence of sex-dependent associations between PNMS related to a flooding disaster and early childhood BMI and adiposity [32]. Similarly, data from the Quebec Ice Storm study ( N  = 111) showed no evidence of sex-dependent associations between disaster-related PNMS and child adiposity or BMI (ages 5–15) [31].…”
Section: Resultsmentioning
confidence: 99%
“…(Note, studies evaluating fetal weight and birth weight were included in the Fetal/Neonatal Health section.) In the Iowa Flood Study ( N  = 106), there was no evidence of sex-dependent associations between PNMS related to a flooding disaster and early childhood BMI and adiposity [32]. Similarly, data from the Quebec Ice Storm study ( N  = 111) showed no evidence of sex-dependent associations between disaster-related PNMS and child adiposity or BMI (ages 5–15) [31].…”
Section: Resultsmentioning
confidence: 99%
“…1. Full text review yielded 24 publications for inclusion into the systematic review and meta-analyses [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58]. The list of excluded studies with reasons for exclusion is available in SI 5.…”
Section: Eligible Studies and Characteristicsmentioning
confidence: 99%
“…We performed two separate meta-analyses for BMI and body fat datasets. Table 1 altogether with SI 6 illustrate the characteristics of the 19 included studies [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,53,55,56,58]. Thirteen studies included a relatively similar amount of males and females.…”
Section: Figmentioning
confidence: 99%
“…There is growing evidence that prenatal maternal stress (PNMS) due to a natural disaster is linked to adverse fetal development and alterations in child outcomes (Dancause et al, 2015;King et al, 2005;Laplante et al, 2004;Simcock et al, 2017;Simcock et al, 2016). Several studies have linked maternal depression, anxiety and stress in pregnancy with adverse fetal outcomes (Brunton and Russell, 2011;Buss et al, 2010;Davis et al, 2011;O'Connor et al, 2005;Ponder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%